2014
DOI: 10.1002/ijc.28670
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metagenomic analysis of glioblastoma reveals absence of known virus despite antiviral‐like type I interferon gene response

Abstract: Glioblastoma is a deadly malignant brain tumor and one of the most incurable forms of cancer in need of new therapeutic targets. As some cancers are known to be caused by a virus, the discovery of viruses could open the possibility to treat, and perhaps prevent, such a disease. Although an association with viruses such as cytomegalovirus or Simian virus 40 has been strongly suggested, involvement of these and other viruses in the initiation and/or propagation of glioblastoma remains vague, controversial and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…There is a surprising similarity to be drawn between foreign viral nucleotide sequences and select ncRNAs silent in normal cells, yet transcribed in cancer cells, activating innate immunity (23,29,(35)(36)(37). We determined that ncRNAs expressed predominantly in normal cells from humans and mice reflect patterns of nucleotide sequence motif avoidance, such as underrepresentation of CpG-containing sequences and reduced UpA, similar to protein-coding RNA.…”
Section: Discussionmentioning
confidence: 98%
“…There is a surprising similarity to be drawn between foreign viral nucleotide sequences and select ncRNAs silent in normal cells, yet transcribed in cancer cells, activating innate immunity (23,29,(35)(36)(37). We determined that ncRNAs expressed predominantly in normal cells from humans and mice reflect patterns of nucleotide sequence motif avoidance, such as underrepresentation of CpG-containing sequences and reduced UpA, similar to protein-coding RNA.…”
Section: Discussionmentioning
confidence: 98%
“…Most of this debate stems from the fact that different research groups, often using different assays, have generated evidence to support or refute the presence of HCMV in GBM tumors. There is a large amount of research supporting both sides of this issue (Amirian, Bondy, Mo, Bainbridge, & Scheurer, 2014; Baryawno et al, 2011; Baumgarten et al, 2014; Cosset et al, 2014; Fornara et al, 2016; Hashida et al, 2015; Holdhoff et al, 2015; Joseph, McDermott, Baryshnikova, Cobbs, & Ulasov, 2017; Khoury et al, 2013; Lehrer, Green, Rosenzweig, & Rendo, 2015; Libard et al, 2014; McFaline-Figueroa & Wen, 2017; Prins, Cloughesy, & Liau, 2008; Rahbar et al, 2012; Sardi et al, 2015; Schelhorn et al, 2013; Shamran et al, 2015; Solomon, Ramkissoon, Milner, & Folkerth, 2014; Stangherlin et al, 2016; Strong et al, 2016; Wolmer-Solberg et al, 2013) that we summarize in Fig. 1B–D.…”
Section: Introductionmentioning
confidence: 90%
“…Cosset et al, [53] [60] On the other hand, several recent studies have reported no association between HCMV and GBM. One study utilized several approaches including a prospective and retrospective analysis to detect the presence of HCMV in tissue, plasma, and serum of high-grade glioma (HGG) patients.…”
Section: Authors Number Of Samples Analyzed Detection Methods Analytementioning
confidence: 98%